Comparison of Acupressure Effect on Sanyinjiao Point with that of Vitamin E on Primary Dysmenorrhea - Z Bostani khalesi; M Abedinzade; A Safari (Armaghane Danesh Bimonthly Journal, 2009)
Introduction & Objective: Dysmenorrhea is a common gynecologic disorder which at least fifty percent of women experience through their reproductive period. The most important cause of primary dysmenorrhea is the enhancement of prostaglandins production and its role in the appearance of the pain. The purpose of this study was to compare the effect of acupressure and vitamin E in reduction of the severity of pain in primary dysmenorrhea. Materials & Methods: This was a randomized clinical trial study to compare the effect of the pressure point Sanyinjiao medication and vitamin E on dysmenorrhea. In this study, 100 female students between 18 t0 22 years of age were recruited. The students were randomly allocated into two groups: pressure medication group, and vitamin E group. In the first cycle, no treatment was used. But during the next two cycles, with the start of pain in the pressure medication group, the Sanyinjiao point was pressured for 20 minutes and in the Vitamin E group, each subject used one pill of Vitamin E (200 units), daily. The necessary data was collected by questionnaire and Andrish- Millsom scale of dysmenorrhea. Mann-Whitney, Fridman, Wilcoxon, chi-square and t-test were used for data analysis. Results: The present study revealed that there was significant differences in the rate of pain during the cycles in both groups. There was a significant difference in pain intensity for each group before and after the treatment (P<0.05). Significant difference was found between two groups in the duration of pain in second months (P<0.05).